Ca(2+)-dependent inactivation of a cloned cardiac Ca2+ channel alpha 1 subunit (alpha 1C) expressed in Xenopus oocytes. - Neely, A (1994)
The alpha 1 subunit of cardiac Ca2+ channel, expressed alone or coexpressed with the corresponding beta subunit in Xenopus laevis oocytes, elicits rapidly inactivating Ca2+ currents. The inactivation has the following properties: 1) It is practically absent in external Ba2+; 2) it increases with Ca2+ current amplitudes; 3) it is faster at more negative potentials for comparable Ca2+ current amplitudes; 4) it is independent of channel density; and 5) it does not require the beta subunit. These findings indicate that the Ca2+ binding site responsible for inactivation is encoded in the alpha 1 subunit and suggest that it is located near the inner channel mouth but outside the membrane electric field.